Functional connectome fingerprinting: Identifying individuals and predicting cognitive functions via autoencoder - Cai, Biao; Zhang, Gemeng; Zhang, Aiying; Xiao, Li; Hu, Wenxing; Stephen, Julia M.; Wilson, Tony W.; Calhoun, Vince D.; Wang, Yu‐Ping (Human brain mapping, 2021)
Functional network connectivity has been widely acknowledged to characterize brain functions, which can be regarded as “brain fingerprinting” to identify an individual from a pool of subjects. Both common and unique information has been shown to exist in the connectomes across individuals. However, very little is known about whether and how this information can be used to predict the individual variability of the brain. In this paper, we propose to enhance the uniqueness of individual connectome based on an autoencoder network. Specifically, we hypothesize that the common neural activities shared across individuals may reduce the individual identification. By removing contributions from shared activities, inter‐subject variability can be enhanced. Our experimental results on HCP data show that the refined connectomes obtained by utilizing autoencoder with sparse dictionary learning can distinguish an individual from the remaining participants with high accuracy (up to 99.5% for the rest–rest pair). Furthermore, high‐level cognitive behaviors (e.g., fluid intelligence, executive function, and language comprehension) can also be better predicted with the obtained refined connectomes. We also find that high‐order association cortices contribute more to both individual discrimination and behavior prediction. In summary, our proposed framework provides a promising way to leverage functional connectivity networks for cognition and behavior study, in addition to a better understanding of brain functions. Our main contribution is to enhance the individual uniqueness based on a framework applying an autoencoder network. Our approach is validated using six modalities of fMRI (resting‐state 1, resting‐state 2, working memory, motor, language, and emotion) from the HCP data set.